Measurement of Anti-Corruption Literacy Index (ALI) & amp for the Young Generation Based on Perception, Participation - Suriadi, Jadi (Journal of Critical Realism in Socio-Economics (JOCRISE), 2022)
The study is emprical case of Young Generation Anti-Corruption Literacy Index (ALI). it was conducted with a scope of students from SMKN1 Gambut, Banjar, South Kalimantan. The number of registered students is 908, for various reasons it is estimated that only about 900 have reached as the target. The number of responsed collected was 724 or a “response rate” is 80.05%. Answering the question how is the ALI measurement carried out? Researcher describe: 1). By using the wellbeing methodology (WM) approach; 2). Designing object, defining sub-objects (variables) with expert group discussion (EGD); 3). Carry out sociometric measurements and design online e-survey instruments and cloud computing. The measurement includes an assessment based on the perspective of perception, participation and acceptability (PPA) on each variable, using a purposive population. The results of these measurements are then accumulated in the form of an index. This index is a kind of composite index. The value score is a numeric number from a scale of 9, no conversion is carried out, calculated accumulatively, all scores are tested for significance. The significance reference standard (SRS) was used. From the data presented, it can be seen that all scores show a much higher value than the SRS score. This means that the results of ALI for students at SMKN1 Gambut, Banjar are significant. From the comparison of scores, the highest value is on the X5 variable, namely "honestly conveying" with an assessment score of 7.97 (of 9) which is an almost perfect score. Very good. In the perception data, only 4.1% rated score 5 or below it. This means 95.9% of respondents rate 6 and above. The recommendations given by the researcher on the results of the ALI study at SMKN1 Gambut, Banjar, South Kalimantan are as follows: 1). Public Research, by e-Survey need to be conducted regularly (6 months) and continuously. If a students are in vocational school for 3 years, they will receive introduction and education of ALI for 6 times; 2). Schools need to conduct public research independently, via the school student council and collaborate with parties when necessary. To embed an anti-corruption attitude for the younger generation. The school publishes to students. Public Research is a kind of Open Science. The openness of knowledge is increasingly widespread in the digital era; 3). As an effort to participate in civil society, in this case schools are to help the government suppress extraordinary crimes (corruption, drugs and terrorism). Public research, is research that is easy, cheap and fast.